MENGUNGKAP KEBERHASILAN PENGELOLAAN DANA DESA PADA DESA GALALA DAN NEGERI LATUHALAT (STUDI KASUS) - Jefry Gasperz; Marsya Ester Dominique Tibalia (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to examine how village funds are managed in the villages of Galala and Negeri Latuhalat, so that they become successful villages in the management and flow of village fund management facilities in the two villages. The method used is a qualitative method with a descriptive research type. The results of this study indicate that success in managing village funds is complying with existing legal regulations. In addition, there are factors that form the background and form the basis for good governance of village funds, namely the principle of accountability, the principle of transparency and the principle of participation. number 20 of 2018 concerning village financial management, accountability for the management of these two villages consists of several stages, namely planning, implementation and reporting. Transparency in the management of village funds in both villages is good with notice boards usually placed at the village hall or in strategic places, while village community participation has been carried out starting from decision making, participation in implementation to participation in evaluation.